Pemberdayaan Kewirausahaan Bagi Ibu PKK Melalui Pelatihan Es Coklat Kakao Di Desa Pandan Krajan Mojokerto - Ikka, Ni Dewi Ambal; Utomo, Budi; Anam, Khoirul; Mulyono, Joko Sri; Soesanto, Soesanto; Novita, Mega Darmi; Purwanti, Sri (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Women's empowerment is crucial in boosting the local economy, including in Pandan Krajan Village. Cocoa products that are still not maximally utilized by the community can be of economic value to the family and the income of a village community. The purpose of this service activity is to empower entrepreneurship for PKK mothers through cocoa ice chocolate training. The service was carried out in Pandan Krajan Village, Kemlagi District, Mojokerto Regency in December 2024. Women's Empowerment with PKK mothers who have an interest in entrepreneurship. The entrepreneurship empowerment program for PKK mothers in home-based businesses through cocoa chocolate ice training in Pandan Krajan Village is a cocoa chocolate ice training program implemented in Pandan Krajan Village has shown positive results in empowering PKK mothers. The conclusions that can be presented from this service program are Skills Improvement, Income Source Creation, Social Empowerment, and Model Inspiration for Other Villages.